Pemberdayaan Masyarakat Desa Pangalli Melalui Digitalisasi dan Pelestarian Kearifan Lokal - Nurul Ismi Putri M; Diyana; Ayu Andira (Lembaga Penelitian Pengabdian kepada Masyarakat, 2025)
Abstract The rapid development of information technology in the era of globalization demands that rural communities possess adequate digital literacy skills to support technology-based development. However, disparities in access to and utilization of technology remain evident in many rural areas, including Pangalli Village, Walenrang Timur District, Luwu Regency. This condition prompted the implementation of the 2025 Thematic Community Service Program (Kuliah Kerja Nyata or KKN) of UIN Palopo under the theme Smart Village and Local Wisdom, which focuses on empowering communities through two main aspects: village digitalization and the preservation of local wisdom. The program employed the Asset-Based Community Development (ABCD) approach, emphasizing the strengthening of local potential and community participation as active subjects of development. The implementation methods included participatory observation, informal interviews, and documentation, conducted through several stages inculturation, asset mapping, planning, implementation, and participatory reflection. The results indicate that the digitalization program successfully improved community skills in digital content creation and expanded the reach of micro-enterprises through business location tagging on Google Maps. Meanwhile, in the aspect of local wisdom preservation, activities such as the Festival Anak Saleh, Independence Day competitions, and the development of Family Medicinal Gardens (TOGA) effectively strengthened social values and community cooperation. Overall, the KKN activities in Pangalli Village successfully integrated digital innovation with cultural preservation, forming an adaptive, participatory, and sustainable model of community empowerment toward realizing the concept of a Smart Village based on local wisdom. Keywords: community empowerment, village digitalization, local wisdom, Smart Village, ABCD approach.